LGBTQ Community Archives in Small Urban Centers: Reflections on Community and University Partnerships to Build Awareness of the Lehigh Valley’s Rich LGBTQ History from AIDS Activism to Anti-Discrimination Legislation - Mary Foltz; Susan Falciani Maldonado; Kristen Leipert; Rachel Hamelers; Adrian Shanker (European Journal of American Studies, 2022)
Too frequently regional LGBTQ history outside of major metropolises is not a major focus either in university curriculum or for financially strapped local non-profit organizations as they provide essential direct services to our communities. Even as the late twentieth and early twenty-first century have ushered in a new focus on local archival projects, regional organizations often struggle to find funding for local historical projects while universities provide LGBTQ studies courses that center activism in NYC, Los Angeles, or San Francsico, marches in Washington, D.C., and the value of subcultural spaces on the coasts. As scholars have argued in the past decade, literary critics and historians need to focus more attention on LGBTQ activism, cultural production, and community formations outside of major urban centers. For university faculty, staff, and archivists, we have the opportunity to address this need by partnering with regional LGBTQ organizations, using our resources to help build strong local archives, and working with community members to shape narratives about LGBTQ history that engage with national movements while also addressing the nuances of activist work in various cultural contexts. This article addresses how community center leaders, archivists, faculty, and students in Allentown, PA have collaborated to meet these challenges by discussing three impactful archival projects: F.A.C.T. (Fighting AIDS Continuously Together) public history courses, an exhibit titled “Pride Guides and the Early Years of Lehigh Valley Pride Festivals,” and the Lehigh Valley LGBT Community Oral History Project. As we provide details about these projects, we trace the value of centering regional AIDS activism, pride celebrations, and struggles for anti-discrimination legislation for our regional LGBTQ community and our students. We argue that courses, exhibits, and oral history collection not only produce regional connectivity to national political projects and strategies, but also build stronger understanding of the import of local activism for promoting equity at the civic and state level. Beyond understanding the historical trajectory of regional activism, archival work and exhibitions bring diverse young people, elders, and those in the middle of life together who may not have met otherwise to reflect on our history and to imagine our future. The process of incorporating students, organizational leaders, and archivists in shared historical projects and narratives formation builds new networks for meeting urgent present-day needs.